The LacZ plasmid-based transgenic mouse model: an integrative approach to study the genotoxicity of nanomaterials - Louro, Henriqueta (2014)
Numerous in vitro studies have been performed to address the potential genotoxicity of chemicals and of emerging products, e.g., nanomaterials. Although valuable for hazard assessment, the in vitro assays do not reflect the complexity of an organism, including, bioavailability, toxicokinetics and immune responses. Moreover, the biological effects at the target organs are known to be greatly influenced by factors as cell proliferative rate, metabolic and DNA repair capacities. In this sense, data from suitable in vivo assays are useful to evaluate the performance of in vitro assays and to strengthen the knowledge about the genotoxicity of chemicals and nanomaterials, using several routes of exposure, at a whole organism level. This chapter provides an overview of an integrated experimental design, based on the use of a LacZ-plasmid based transgenic mouse model to investigate multiple genotoxicity endpoints in several organs, towards the safety evaluation of nanomaterials. This approach includes the analysis of chromosome instability, assessed by the micronucleus assay in blood or bone marrow cells and by sister chromatid exchanges in splenocytes, the analysis of DNA breaks and oxidative DNA damage by the comet assay, and the quantification of gene mutations in multiple organs. Furthermore, histological markers e.g., of inflammation and apoptosis, can add information about other relevant cell responses. A key point is that all assays are performed on the same animal, therefore increasing the efficiency while reducing the cost and the number of animals under experimentation, in compliance with the EU recommendations. Overall, gathering the data from the several endpoints and organs of the same animal depicts the complex response of a whole-organism to nanomaterials exposure, thereby providing a better prediction of the effects on humans.